2004
DOI: 10.1242/jcs.01109
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent Ca2+ oscillations in mouse embryos are regulated by nuclear targeting of PLCζ

Abstract: During the first cell cycle Ca2+ oscillations are regulated in a cell cycle-dependent manner, such that the oscillations are unique to M phase. How the Ca2+ oscillations are regulated with such cell cycle stage-dependency is unknown, despite their importance for egg activation and embryo development. We recently identified a novel, sperm-specific phospholipase C (PLCzeta; PLCζ) that triggers Ca2+ oscillations similar to those caused by sperm. We show that PLCζ-induced Ca2+ oscillations also occur exclusively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 41 publications
5
110
1
Order By: Relevance
“…Repetitive Ca 2+ oscillations occur immediately following fertilisation in mammalian oocytes, and are believed to be driven by InsP 3 production that is caused by the introduction of PtdIns-PLCζ into the oocyte from the fused sperm. The Ca 2+ oscillations cease around the time when the pronucleus is formed, owing to the sequestration of PtdIns-PLCζ in the nucleus (Larman et al, 2004). Unlike the other PtdIns-PLC isozymes described above, when PtdIns-PLCζ is in the nucleus, it does not evoke InsP 3 production and Ca 2+ signalling.…”
Section: Autonomous Generation Of Ca 2+ -Mobilising Messengers In Thementioning
confidence: 89%
“…Repetitive Ca 2+ oscillations occur immediately following fertilisation in mammalian oocytes, and are believed to be driven by InsP 3 production that is caused by the introduction of PtdIns-PLCζ into the oocyte from the fused sperm. The Ca 2+ oscillations cease around the time when the pronucleus is formed, owing to the sequestration of PtdIns-PLCζ in the nucleus (Larman et al, 2004). Unlike the other PtdIns-PLC isozymes described above, when PtdIns-PLCζ is in the nucleus, it does not evoke InsP 3 production and Ca 2+ signalling.…”
Section: Autonomous Generation Of Ca 2+ -Mobilising Messengers In Thementioning
confidence: 89%
“…Larman et al addressed this question in a 2004 study [14]. They observed that Ca 2+ oscillation was obtained pluripotency, we must understand the two-calcium-pool model of Ca 2+ oscillation, because Ca 2+ oscillation is thought to be a necessary and sufficient condition in the creation of pluripotency.…”
Section: A Role For Cell's Water Property In Proton/calcium Signalingmentioning
confidence: 99%
“…What is the difference between the two (M vs. G1/G2)? A few hypotheses have been put forth [14,15], but in the next section we propose a new model based on the water state in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…After a false start (Parrington et al 1996;Shevchenko et al 1998), the active component was identified as a novel phospholipase C, PLCz, that was present only in the testis and the sperm (Rice et al 2000;Saunders et al 2002). This entirely specific tissue distribution argues very strongly that PLCz is the activating agent in mammalian fertilization; there is other indirect evidence: PLCz is sequestered into the zygote nucleus as it reforms after fertilization just as the fertilization calcium transients are dying away; if sequestration is prevented, the transients persist (Kono et al 1995;Larman et al 2004;Saunders et al 2007). It has to be admitted though that the definitive proof by gene knockout is lacking.…”
Section: Initiation and Propagation Of The Fertilization Calcium Wavementioning
confidence: 99%